Comparison of different pheromone dispensers in luring Musca domestica towards delta trap - S.T. Bino Sundar; T.J. Harikrishnan; Bhaskaran Ravi Latha; G. SarathChandra; T.M.A. Senthil Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The house fly sex pheromone (Z)-9-tricosene was impregnated into different pheromone dispensers (septa, plastic and polythene) and their efficacy in luring Muscadomestica towards red acrylic delta trap was studied. Out of the 514 house flies trapped, (Z)-9tricosene when impregnated in circular plastic green lure attracted the maximum number of flies (165), followed by polyvial (132), silicone septa (111) and rubber septa (79) whereas the least number of flies was attracted with rectangular plastic dispenser (27). Among the house flies trapped, 46.49 per cent (239) were males and 53.50 per cent (275) were females redominance of male flies was observed with circular plastic green lure, polyvial and silicone septa, whereas in rubber septa and rectangular plastic lure, more number of female house flies were trapped. Observations revealed that circular plastic green lure, polyvial and silicone septa can be used as an effective dispensers to impregnate (Z)-9-tricosene in order of preference to facilitate slow and sustained release of pheromone and thereby trapping the optimum number of house flies towards delta trap.